2009
DOI: 10.1016/j.solidstatesciences.2009.02.015
|View full text |Cite
|
Sign up to set email alerts
|

The Ba2LnFeNb4O15 “tetragonal tungsten bronze”: Towards RT composite multiferroics

Abstract: Several Niobium oxides of formula Ba 2 LnFeNb 4 O 15 (Ln = La, Pr, Nd, Sm, Eu, Gd) with the "Tetragonal Tungsten Bronze" (TTB) structure have been synthesised by conventional solid-state methods. The Neodymium, Samarium and Europium compounds are ferroelectric with Curie temperature ranging from 320 to 440K. The Praseodymium and Gadolinium compounds behave as relaxors below 170 and 300 K respectively. The Praseodymium, Neodymium, Samarium, Europium and Gadolinium compounds exhibit magnetic hysteresis loops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
92
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 14 publications
13
92
2
Order By: Relevance
“…The diffraction patterns of all composites pellets show that the "pseudo-tetragonal" orthorhombic cell (Pba2 S.G. n°32) previously observed [9] is maintained. For lanthanum composites, the Bragg diffraction peaks related to the fergusonite LaNbO 4 are identified, despite their relative low intensities.…”
Section: X-ray Diffraction Patternsmentioning
confidence: 63%
See 1 more Smart Citation
“…The diffraction patterns of all composites pellets show that the "pseudo-tetragonal" orthorhombic cell (Pba2 S.G. n°32) previously observed [9] is maintained. For lanthanum composites, the Bragg diffraction peaks related to the fergusonite LaNbO 4 are identified, despite their relative low intensities.…”
Section: X-ray Diffraction Patternsmentioning
confidence: 63%
“…We recently have shown that a barium ferrite parasitic phase was responsible for RT magnetic hysteresis [9]. A relationship between the chemical stability of samples.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58][59][60] The above examples demonstrate the intricate relationships between the composition, structure, and properties of TTB systems, which were illustrated in an original way by the study of Ba 2 REFeNb 4 O 15 composite multiferroic ceramics. [61] At room temperature, the crystal structure of Ba 2 REFeNb 4 O 15 was described in a "pseudotetragonal" symmetry, space group Pba2 (no. 32), with a ≈ b = 12.514(1) Å and c = 3.941(1) Å, and there was suspicion of the existence of structural modulations.…”
Section: Wwweurjicorg Full Papermentioning
confidence: 99%
“…32), with a ≈ b = 12.514(1) Å and c = 3.941(1) Å, and there was suspicion of the existence of structural modulations. [61] The Ba 2 REFeNb 4 O 15 family also shows an interesting correlation between structural and dielectric properties, which depends on the size of rare-earth cations. An uncommon evolution from ferroelectric to relaxor properties was found in the related solid solution Ba 2 Pr x Nd 1-x FeNb 4 O 15 .…”
Section: Wwweurjicorg Full Papermentioning
confidence: 99%
See 1 more Smart Citation